Studi Pengaruh Iradiasi Gamma Terhadap Kadar Senyawa Bioaktif dan Aktivitas Antiinflamasi Jahe Merah (Zingiber officinale roscoe) - Aulia Nova Kusumaningtyas; Yahdiana Harahap; Abdul Mun'im; Supandi Supandi (BIOEDUSCIENCE, 2022)
Background: In Indonesia, the use of herbal plants in overcoming several health problems shows a fairly high rate. Red ginger is one of the herbs that is widely consumed and empirically has the property of relieving or reducing inflammation. However, as is well known, in general the microbiological contamination of herbs is quite high. To maintain the quality of herbal plants, special treatment is required, to ensure that microbial contamination is within safe limits. This study aims to determine the effect of gamma irradiation on the number of microbial contamination, and the bioactive content of 6,8,10-gingerol; 6-shogaol in 70% ethanol extract of red ginger, and its activity as an anti-inflammatory. Methodes: Samples of 70% ethanol extract of red ginger were irradiated with various doses of 0, 5, 7.5, 10 and 15 KGy. Microbiological contamination is determined in Total Plate Number and Yeast Mold Number. The content of compounds 6,8,10-gingerol and 6-shogaol was observed by high performance liquid method and their anti-inflammatory activity was observed by protein denaturation inhibition (BSA) method. Results: Gamma irradiation at doses of 0, 5, 7.5, 10 and 15 KGy reduced microbial contamination as the exposure dose increased, and did not affect the levels of bioactive 6,8,10-gingerol; 6-shogaol and its anti-inflammatory activity. The anti-inflammatory activity of 70% ethanol extract of red ginger is influenced by the content of bioactive compounds. Conclusion: Gamma irradiation is effective for decontaminating microbiological contaminants, and improving the quality of red ginger, and does not affect the bioactive levels contained and its anti-inflammatory activity (in vivo).